Menumbuhkan Minat Baca pada Anak SD: Dari Dongeng Hingga Buku Pelajaran - Zhera Auli Ramadhani; Ari Suriani (STIKes Ibnu Sina Ajibarang, 2025)
Reading interest among elementary school children is a fundamental foundation for literacy development and long-term academic success. However, the reading interest of elementary students in Indonesia remains low due to limited engaging reading materials and an unsupportive literacy environment. This study aims to analyze the role of various types of reading materials, such as fairy tales, children’s storybooks, and literate textbooks, in enhancing the reading interest of elementary students. A qualitative descriptive approach was used, collecting data through literature review, observation, and document analysis to depict effective practices in literacy learning. The results show that fairy tales serve as an initial gateway to literacy by building a positive emotional connection to reading, while children’s storybooks strengthen independent reading habits through appealing illustrations and engaging plots. Literate and contextual textbooks broaden literacy scope by integrating everyday experiences. The findings emphasize the importance of selecting reading materials suited to children’s psychological characteristics and the active role of teachers and parents in creating a joyful reading environment. This study provides strategic input for educators and policymakers to improve literacy at the elementary school level.